Distúrbios funcionais da oclusão e sua correlação com radiografias transcranianas da articulação temporomandibular, em pacientes portadores de fissuras labiopalatais - Takahashi, Fernando Eidi [UNESP] (Universidade Estadual Paulista (Unesp), 1993)
Anamnesis, clinical examinations and temporomandibular joint transcraneal radiographs for 22 adults with cleft lip and palate were carried out in order to evaluate the occlusion and correlate it with radographic findings. The conclusions were: 72.8% of the patients have at least one sign or symptom of craniomandibular disorders (CMD); although the occlusal conditions were severely altered, most of the signs and symptoms were classified as mild; the greater frequency of the signs and symptoms occurred among women; in the radiographic evaluation, all of the assymptomatic patients had both condyles with normal contour and all of the patients with altered contour had at least one sign or symptom; the bilateral centered position of the condyles in the fossa e did not warrant the absence of signs and symptoms; some patients with bilateral condyles positioned posteriorly or caudally or even assimetrically, did not present signs and symptoms of dysfunction; the radiographic findings should be correlated with clinical findings; and a great number of patients were not observed with clinical board of C:MD caused by the occlusion. Key words: Radiography; temporomandibular joint; temporomandibular joint syndrome; cleft palate; dental occlusion

Foram avaliados 22 adultos portadores de fissuras labiopalatais, através de anamnese, exame clínico e radiografias transcranianas da articulação temporomandibular, com o intuito de observar a oclusão e correlacioná-la ccom os achados radiográficos. Os dados obtidos permitiram concluir que: 72,8% dos pacientes apresentavam, pelo menos, um sinal ou sintoma de disfunção craniomandibular (DCM); embora a condição oclusal se apresentasse severamente comprometida a maioria desses sinais ou sintomas era suave; a maior frequência dos sinais ou sintomas ocorreram no sexo feminino; na avaliação radiográfica, todos os pacientes assintomáticos apresentavam os dois côndilos com contorno normal, e todos os que apresentavam alteração de contorno, possuíam pelo menos um sinal ou sintoma de DCM; a posição centrada bilateral dos côndilos na fossa mandibular, não garante a ausência de sinais e sintomas de DCM; alguns pacientes com côndilos posicionados bilateralmente, para posterior ou, para caudal ou ainda, assimétricos, não apresentavam sinais ou sintomas de DCM; os achados radiográficos devem ser correlacionados com os achados clínicos; não foi observado um número significativo de pacientes com quadro clínico de DCM de origem oclusal
Keywords: Oclusão (Odontologia); Articulação temporomandibular; Radiografia; Occlusion (Dentistry)